2016
DOI: 10.1080/03601234.2016.1224701
|View full text |Cite
|
Sign up to set email alerts
|

Advantages and risks of using steel slag in preparing composts from raw organic waste

Abstract: It had been reported that iron and manganese oxides in steel slag enhanced the production of humic acid (HA) from low-molecular-weight compounds, such as phenolic acids, amino acids, and saccharides. In the present study, this function of steel slag was applied to the composting of raw organic wastes (ROWs). The degree of humification of HAs is an important factor in evaluating compost quality. Thus, HAs were extracted from the prepared composts and the humification parameters were determined, in terms of elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…BOF slag is generated by an integrated steel mill, and it approximately accounts for half of the total steel slag output in the world. Many studies have reported that the major constituents of steel slag are typically calcium, silicon, and iron compounds, and some heavy metals, such as chromium, manganese, barium, zinc, and vanadium, are present at trace levels . Steel slag are usually reused or recycled for cement production, road construction, hydraulic engineering works, construction fills, fertilizers, and other applications .…”
Section: Introductionmentioning
confidence: 99%
“…BOF slag is generated by an integrated steel mill, and it approximately accounts for half of the total steel slag output in the world. Many studies have reported that the major constituents of steel slag are typically calcium, silicon, and iron compounds, and some heavy metals, such as chromium, manganese, barium, zinc, and vanadium, are present at trace levels . Steel slag are usually reused or recycled for cement production, road construction, hydraulic engineering works, construction fills, fertilizers, and other applications .…”
Section: Introductionmentioning
confidence: 99%